Controlled Heat and Humidity-Based Treatment for the Reuse of Personal Protective Equipment: A Pragmatic Proof-of-Concept to Address the Mass Shortage of Surgical Masks and N95/FFP2 Respirators and to Prevent the SARS-CoV2 Transmission - Bernard, Louis; Desoubeaux, Guillaume; Bodier-Montagutelli, Elsa; Pardessus, Jeoffrey; Brea, Déborah; Allimonnier, Laurine; Eymieux, Sébastien; Raynal, Pierre-Ivan; Vasseur, Virginie; Vecellio, Laurent; Mathé, Ludovic; Guillon, Antoine; et al. (Frontiers in Medicine, 2020)
Background: The coronavirus infectious disease-2019 (COVID-19) pandemic has led to an unprecedented shortage of healthcare resources, primarily personal protective equipment like surgical masks, and N95/filtering face piece type 2 (FFP2) respirators. Objective: Reuse of surgical masks and N95/FFP2 respirators may circumvent the supply chain constraints and thus overcome mass shortage. Methods, design, setting, and measurement: Herein, we tested the effects of dry- and moist-air controlled heating treatment on structure and chemical integrity, decontamination yield, and filtration performance of surgical masks and FFP2 respirators. Results: We found that treatment in a climate chamber at 70°C during 1 h with 75% humidity rate was adequate for enabling substantial decontamination of both respiratory viruses, oropharyngeal bacteria, and model animal coronaviuses, while maintaining a satisfying filtering capacity. Limitations: Further studies are now required to confirm the feasibility of the whole process during routine practice. Conclusion: Our findings provide compelling evidence for the recycling of pre-used surgical masks and N95/FFP2 respirators in case of imminent mass shortfall.